Manejo de heridas con sacarosa y su efectividad en la práctica clínica (2022)
Since the dawn of humanity more than 4,000 years ago, in ancient civilizations sugar was used daily to treat wounds that were very frequent at the time, due to the workload necessary for subsistence. These wounds were not only present in humans but also in working animals, in which case, they were the first to be experimented on in wound management; to later be extrapolated to human clinical practice